2009
DOI: 10.1155/2009/408794
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cells Overexpressing FGF‐2 Alone or Combined with Manual Stimulation Do Not Promote Functional Recovery after Facial Nerve Injury

Abstract: Purpose. To determine whether transplantation of Schwann cells (SCs) overexpressing different isoforms of fibroblast growth factor 2 (FGF-2) combined with manual stimulation (MS) of vibrissal muscles improves recovery after facial nerve transection in adult rat. Procedures. Transected facial nerves were entubulated with collagen alone or collagen plus naïve SCs or transfected SCs. Half of the rats received daily MS. Collateral branching was quantified from motoneuron counts after retrograde labeling from 3 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The combination of morphological and quantitative evaluation of selective reinnervation of the target musculature by retrograde fluorescence tracing and functional assessment by digital motion analysis of the vibrissae allows a precise estimation of the quality of facial nerve regeneration. 3,[16][17][18] Previously, we have shown that terminal sprouting at the end plates of the target musculature is also an important factor influencing the degree of defective healing after nerve regeneration. 3 This and the role of the supraspinal centers controlling locomotion of the whiskers [19][20][21][22][23] was not analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of morphological and quantitative evaluation of selective reinnervation of the target musculature by retrograde fluorescence tracing and functional assessment by digital motion analysis of the vibrissae allows a precise estimation of the quality of facial nerve regeneration. 3,[16][17][18] Previously, we have shown that terminal sprouting at the end plates of the target musculature is also an important factor influencing the degree of defective healing after nerve regeneration. 3 This and the role of the supraspinal centers controlling locomotion of the whiskers [19][20][21][22][23] was not analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, this does not appear to be the case in the nerve regeneration research and, espe-cially in recent years, several papers have been published reporting negative results after various tissue engineering approaches in experimental animal models Grosheva et al, 2008;Haastert et al, 2009;Sinis et al, 2008Sinis et al, , 2009Skouras et al, 2009). …”
Section: The Importance Of Publishing Negative Results In Nerve Tissumentioning
confidence: 99%
“…This review presents an overview of nowadays gene therapy for peripheral nerve injury. The use of this therapeutic strategy holds great hope in the nerve repair field because it lies mainly in providing prolonged extra bioactive trophic factors support, within the site of injury, resulting in the improvement of survival of sensory and motor neurons and SCs; increased SC motility; axon regrowth and remyelination; reinnervation; and, ultimately, functional recovery [15,17,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], as shown in Table 1.…”
Section: Gene Therapy For Nerve Lesionsmentioning
confidence: 99%